Shared Heraldry and the Sacred Space: The Building Blocks of João I of Portugal’s Imagery - Metelo de Seixas, Miguel (Eikón / Imago, 2024)
This study considers the practice of shared heraldry as an instrument of affirmation of late-medieval monarchies, examining the case study of King João I of Portugal. The study of how this sovereign’s heraldry was shared with those close to him illustrates how heraldry was understood as an instrument of propaganda for the cause of independence, in the context of the 1383-1385 dynastic crisis, and subsequently in building the imagery of the King and the dynasty he founded. The transposition of this heraldry to the Monastery of Batalha, erected to commemorate the victory at Aljubarrota and later a dynastic necropolis, established a privileged relationship with this monument’s architecture and iconography, expanding the same theme of shared heraldry (now in a dynastic context) as an expression of the royal power’s legitimacy.